CITIZEN HATCHERY UNIT SUMBER MINA LESTARI PARTNERSHIP, DAU SUB DISTRICT, MALANG REGENCY - Tiwi Nurjannati Utami (Faculty of Fisheries and Marine Science, Brawijaya University, 2017)
The aims of the research are to know and to analize 1) “UPR Sumber Mina Lestari” partnership pattern, 2) stake holder role on “UPR Sumber Mina Lestari”, 3) strengthen effort on “UPR Sumber Mina Lestari”. The research use descriptive qualitative method. The data collected by interview, observation, and literature study. The research show that “UPR Sumber Mina Lestari” is hatchery fishes group with “Nila Gift” as primary comodities. Partnership pattern on the group is contract partnership with synergy type. UPR have a role as fasilitator for the members. UPR produce fish seeds and fish feeds for the members, build good relation with fish medicine seller, marketing institution, government, researcher and academician and bank. Stake holder have role as supporter that accelerate the business. Government, researcher and academician give information, knowledge and skill to the members; bank give loans with UPR as assurance for the members; and marketing institution buy the product pass through UPR. To strengthen the group, they need to develop the partnership pattern, such as 1) follow choaching from government, researcher or academician actively, especially on hathery technique and business financial, 2) bring about government program that empowerment small scale entreprises, 3) establish cooperation in order to increase the capital, 4) establish new business sub unit like processing fish food, fish restaurant, and education tourism of fresh water fish pond.Key words: partnership, citizen hatchery unit, contract partnership, synergy tipe, stakeholder